The will of the Catholic Monarch and the Aragonese legitima - Sáenz de Santa María Vierna, Alberto (Revista de derecho aragonés, 2016)
Aragonese legal specificities as a identity element. The death of King Carlos II opened a dynastic crisis, whose triggered a deep legal crisis in Aragonese territo- ries, specially after the imposition of the royal decrees of conquest in 1707. The reaction of the Aragonese jurists to the new legal order that sought to legitimize the construction of the new State Bourbon was led by Diego Franco de Villalba, who wrote a trascendental manifesto called Crisis legal that contributed decisively to the pardon to Aragonese private law granted by King Felipe V in 1711.